Governança corporativa eletrônica e desempenho econômico e financeiro das empresas listadas no índice Bovespa - Zago, Carine (2014)
This research is the research on the concept of electronic governance and its practical influence on the performance of listed companies in IBOVESPA. Are discussed in the theoretical framework the concepts of corporate governance and e-governance which are essential for the definition of electronic governance, also discusses about performance and its indicators. Goals as we seek to verify the influence of electronic governance index - IGCE indicators of economic and financial performance of companies listed on Bovespa Index for the years 2012 to 2014. In addition to identifying the key performance indicators used in the literature as well as contribute to the improvement of the theoretical construct on electronic governance. Means choosing a methodology for a quantitative approach, using the statistical method, with reference to the rate of electronic governance (IGCE), 2011, 2012 and 2013, comprising 55 practices collected on the websites of corporations listed on the Bovespa. The unit of analysis comprises the websites of the Bovespa index components companies in March 2012, 2013 and 2014 totaling 48 companies. To verify the issue addressed in the study, we used the statistical technique of regression with panel data, with the aid of Stata and SPSS software. The performance indicators used as dependent variables were the Return on Assets, Return on Equity, Net Margin, Market Value Added, Economic Value Added and Return and Beta of assets, and as the independent variable, governance index electronic corporate. After running the tests was possible to verify that the regressions with the ML variables, EVA, MVA and BETA were not statistically significant at a level of 5%, the ROA and ROE variables were statistically significant, but did not meet the assumptions of the regression model with panel data. Regression to the CAPM variable met all model assumptions with panel data, showing that the electronic corporate governance practices have a negative influence on the risk of the assets of the companies comprising the IGCE. Noting that the more electronic corporate governance practices and fuller they are deployed, the greater will be the expected return on investment and lower the risk.